Improved Thin-Layer Technique for Detection of Arginine Dihydrolase Among the Pseudomonas Species - Zolg, W. (1973)
The detection of arginine dihydrolase among Pseudomonas spp. by thin-layer chromatography is described. The method is based on the procedure of Williams and co-workers (1971) but was improved in sensitivity by selection of a better solvent system.